Ultraefficiently Calming Cytokine Storm Using Ti3C2Tx MXene. Issue 5 (18th January 2021) - Wang, Tianyi; Sun, Xiaoyu; Guo, Xin; Zhang, Jinqiang; Yang, Jian; Tao, Shouxuan; Guan, Jun; Zhou, Lin; Han, Jie; Wang, Chengyin; Yao, Hang; Wang, Guoxiu
Abstract: During the global outbreak of COVID‐19 pandemic, "cytokine storm" conditions are regarded as the fatal step resulting in most mortality. Hemoperfusion is widely used to remove cytokines from the blood of severely ill patients to prevent uncontrolled inflammation induced by a cytokine storm. This article discoveres, for the first time, that 2D Ti3 C2 T x MXene sheet demonstrates an ultrahigh removal capability for typical cytokine interleukin‐6. In particular, MXene shows a 13.4 times higher removal efficiency over traditional activated carbon absorbents. Molecular‐level investigations reveal that MXene exhibits a strong chemisorption mechanism for immobilizing cytokine interleukin‐6 molecules, which is different from activated carbon absorbents. MXene sheet also demonstrates excellent blood compatibility without any deleterious side influence on the composition of human blood. This work can open a new avenue to use MXene sheets as an ultraefficient hemoperfusion absorbent to eliminate the cytokine storm syndrome in treatment of severe COVID‐19 patients. Abstract : During the global outbreak of COVID‐19 pandemic, "cytokine storm" conditions are regarded as the fatal step resulting in most mortality. This article discovers, for the first time, that 2D Ti3 C2 T x MXene nanosheets demonstrate an ultrahigh removal capability for typical cytokine interleukin‐6.